2021
DOI: 10.1515/pjbr-2021-0018
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of using a social robot to teach music to children with low-functioning autism

Abstract: This article endeavors to present the impact of conducting robot-assisted music-based intervention sessions for children with low-functioning (LF) autism. To this end, a drum/xylophone playing robot is used to teach basic concepts of how to play the instruments to four participants with LF autism during nine educational sessions. The main findings of this study are compared to similar studies conducted with children with high-functioning autism. Our main findings indicated that the stereotyped behaviors of all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 41 publications
1
25
0
1
Order By: Relevance
“…The participants were children and young teens who had been diagnosed with ASD; the age range was 3-14 years and the mean age 7.27 years. In three studies, the researchers reported that the participants were low-functioning (Duquette et al, 2008;Shamsuddin et al, 2013;Taheri et al, 2021), while in one they were specifically described as high-functioning (Shamsuddin et al, 2012). In the study of Taheri et al (2018), the participants were a pair of high-and low-functioning fraternal twins (Taheri et al, 2018).…”
Section: Characteristics Of Participantsmentioning
confidence: 99%
See 4 more Smart Citations
“…The participants were children and young teens who had been diagnosed with ASD; the age range was 3-14 years and the mean age 7.27 years. In three studies, the researchers reported that the participants were low-functioning (Duquette et al, 2008;Shamsuddin et al, 2013;Taheri et al, 2021), while in one they were specifically described as high-functioning (Shamsuddin et al, 2012). In the study of Taheri et al (2018), the participants were a pair of high-and low-functioning fraternal twins (Taheri et al, 2018).…”
Section: Characteristics Of Participantsmentioning
confidence: 99%
“…The ten studies included in the review took place in six countries on three continents. Three studies were carried out in Malaysia (Ismail et al, 2012;Shamsuddin et al, 2012;Shamsuddin et al, 2013), two in the USA (Srinivasan et al, 2015;Stanton et al, 2008) and Iran (Taheri et al, 2018;Taheri et al, 2021) and one in Canada (Duquette et al, 2008), Luxemburg (Costa et al, 2018) and Romania (David et al, 2020). The distribution indicates the worldwide research interest in studying the effect of REIs on RSBs in children with ASD.…”
Section: Country Of Studymentioning
confidence: 99%
See 3 more Smart Citations